NFB-17. MEK INHIBITOR BINIMETINIB SHOWS CLINICAL ACTIVITY IN CHILDREN WITH NEUROFIBROMATOSIS TYPE 1- ASSOCIATED PLEXIFORM NEUROFIBROMAS: A REPORT FROM PNOC AND THE NF CLINICAL TRIALS CONSORTIUM. (4th December 2020) - Mueller, Sabine; Reddy, Alyssa T; Dombi, Eva; Allen, Jeffrey; Packer, Roger; Clapp, Wade; Goldman, Stewart; Schorry, Elizabeth; Tonsgard, James; Blakeley, Jaishri; Ullrich, Nicole J; Gross, Andrea; et al.
Abstract: BACKGROUND: Plexiform neurofibromas (PNs) can cause significant morbidity. In this phase 2 study, we assessed imaging and functional outcomes to the MEK-inhibitor Binimetinib in pediatric patients with PNs. METHODS: Children (age 1–17 years) with PN that were progressive or causing significant morbidity were eligible. Binimetinib is dosed twice-daily (starting dose of 32mg/m 2 ) for maximum of 24 four-week courses. Participants with partial response (PR; >20% decrease in PN volume on central MRI review) at cycle 12 may stay on therapy. Participants undergo MRI and functional assessments at baseline and after courses 4, 8, 12, 18 and 24. Functional assessments are based on PN location. RESULTS: Here we present 1-year response data. Twenty participants (55% male) with median age 12 years (range 2–16 years) enrolled; 19 are evaluable for response. Median baseline tumor volume was 326 ml (range, 8-6661 ml). Fourteen participants (74%) met criteria for PR, with 11 achieving PR by course 5. Median maximal PN volume reduction was 25.5% (range, 9–54%). As of August 2020, 14 participants received at least 12 cycles of Binimetinib; 10 remain on therapy. Off study reasons include treatment associated toxicities (n=2), subject withdrawal (n=2), non-compliance (n=2), prolonged treatment delay (n=1), and lack of response (n=3). Thirteen participants underwent dose reduction. Institution-reported related grade 3 toxicities included dry skin, weight gain, muscle weakness, rash, paronychia, cellulitis, diarrhea, gastric hemorrhage and CPK increase. CONCLUSIONS: Binimetinib appears reasonably well-tolerated and shows promising activity in children with NF1-associated PNs. Outcomes on functional improvement will be reported at the meeting.